Preparation method and application of Gd-doped rutile ruthenium dioxide nanosheet

By doping Gd in the ruthenium dioxide catalyst and preparing rutile ruthenium dioxide nanosheets by salt template method, the existing catalysts have solved the problem of structural collapse and stability deterioration under high oxidation potential, and achieved efficient catalytic performance of electrolytic water hydrogen production.

CN119663364AActive Publication Date: 2025-03-21GUIZHOU UNIV

Patent Information

Application Number
CN202510074843.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-21
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing ruthenium dioxide catalysts are prone to oxidation under high oxidation potential, resulting in crystal structure collapse and deterioration of stability, limiting their application in electrolyzing hydrogen production.

Method used

RuCl3 and GdN3O9 were used as raw materials to prepare Gd-doped rutile ruthenium dioxide nanosheets by salt template method, and Gd-RuO2 composite material was obtained through the preparation of precursor solution, stirring reaction, purification, calcination and annealing.

Benefits of technology

It achieves an overpotential of only 230mV at a current density of 10mA cm-2, with excellent oxygen evolution performance, conductivity, potential window and redox reversibility, and improves the stability and performance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663364A_ABST
    Figure CN119663364A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Gd-doped rutile type ruthenium dioxide nanosheet, and the Gd-doped rutile type ruthenium dioxide nanosheet is successfully prepared by taking RuCl3 and GdN3O9 as raw materials and adopting a salt template method. When being used as an oxygen evolution catalyst for producing hydrogen by electrolyzing water, the oxygen evolution catalyst shows excellent (OER) oxygen evolution performance, realizes the overpotential of 230mV under the current density of 10mA cm <-2 >, and has excellent conductivity, wider potential window and high redox reversibility, thereby having a wide application prospect in the field of electrocatalysis. In addition, the preparation method disclosed by the invention has the characteristics of simple process steps, safety, easiness in control, easiness in obtaining raw materials, few chemical reagents used in the whole preparation process, small environmental pollution, mild experimental conditions, relatively short time consumption, low cost and the like, so that the preparation method is suitable for industrial popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthesis of ruthenium dioxide nanomaterials, and particularly relates to a preparation method and application of a Gd-doped rutile ruthenium dioxide nanosheet. Background Art

[0002] Hydrogen production by water electrolysis is an effective method to obtain clean energy. The water electrolysis reaction is divided into the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). Among them, the anode oxygen evolution reaction (OER) involves a four-electron transfer process. Therefore, this half-reaction has problems such as slow kinetics and high overpotential. Catalysts are often introduced to accelerate the process to reduce the overpotential of the water electrolysis reaction.

[0003] Ruthenium dioxide has two variants, one is amorphous and the other is a tetragonal system with a rutile structure. Ruthenium dioxide has a strong ability to resist electron transfer. Ruthenium dioxide has the advantages of ultra-high mass specific capacitance, excellent conductivity, wide potential window, and high redox reversibility. It is often used as an electrocatalyst for oxygen evolution reaction in the electrolysis of water to produce hydrogen. There are many methods for preparing ruthenium dioxide, such as sol-gel method, direct oxidation method, electrochemical precipitation method, calcination method, etc. The morphology of the obtained ruthenium dioxide is very different due to different preparation methods, and its electrochemical properties are also very different. Among them, the particles of ruthenium dioxide prepared by calcination and direct oxidation are larger, the grain shapes are quite different, the particle size distribution is uneven, and the particle size cannot be effectively controlled; hydrolysis of chlororuthenic acid is the currently widely used method for preparing ruthenium dioxide in the industry. The disadvantage of this preparation method is that it will produce more harmful pollutants, and the uneven particle size distribution of the obtained ruthenium dioxide powder leads to poor resistance film surface; precipitation method is the most widely used method for liquid phase chemical synthesis of high-purity nanoparticles. Its process is simple and the obtained powder has good performance, but this method still cannot solve the problem of nanoparticle agglomeration.

[0004] Nanosheets have shown superior performance in the application of water electrolysis hydrogen production catalysts due to their low-dimensional structure and highly exposed active sites, and are expected to become a new type of efficient water electrolysis hydrogen production catalyst material.

[0005] However, in practical applications, RuO2 is easily oxidized to high-valent RuO4 at high oxidation potentials, causing the metal to detach from the crystal lattice and become a soluble metal cation. This leads to the collapse of the RuO2 crystal structure and the deterioration of its stability, which severely limits the practical application of proton exchange membrane water electrolyzers (PEMWE). Summary of the invention

[0006] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a preparation method and application of Gd-doped rutile ruthenium dioxide nanosheets.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing Gd-doped rutile ruthenium dioxide nanosheets, comprising the following steps:

[0009] S1, dissolving RuCl3 and GdN3O9 in a solvent to prepare a precursor solution;

[0010] S2. Add the obtained precursor solution into NaCl, stir to react, purify, and calcine and anneal to obtain a Gd-RuO2 composite material, i.e., Gd-doped rutile ruthenium dioxide nanosheets.

[0011] Preferably, the mass volume ratio of RuCl3, GdN3O9, solvent and NaCl is in the range of 0.08g-0.12g: 0.001g-0.003g: 20ml-30ml: 45g-55g.

[0012] Preferably, in step S2, before adding the obtained precursor solution to NaCl, the precursor solution is ultrasonically treated for 15 to 35 minutes.

[0013] Preferably, in step S2, the solvent is any one of water, methanol, ethanol, acetone and ethyl acetate.

[0014] Preferably, in step S2, the temperature during the stirring reaction is 60-90° C., and the stirring reaction time is 3-6 hours.

[0015] Preferably, in step S2, the purification includes: washing, centrifuging and drying the reaction product.

[0016] Preferably, the drying temperature is 60-70° C., and the drying time is 12-18 hours.

[0017] Preferably, the calcination and annealing treatment is carried out in air at a calcination and annealing temperature of 350-500°C.

[0018] The second aspect of the present invention is to provide Gd-doped rutile ruthenium dioxide nanosheets prepared by the above preparation method.

[0019] The third aspect of the present invention is to provide the use of the above-mentioned Gd-doped rutile ruthenium dioxide nanosheets as a catalyst in the electrolysis of water to produce hydrogen.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention uses RuCl3 and GdN3O9 as raw materials and adopts a salt template method to successfully prepare a Gd-RuO2 composite material, that is, Gd-doped rutile ruthenium dioxide, and the microscopic morphology of the obtained Gd-doped rutile ruthenium dioxide is a nanosheet structure.

[0022] (2) The preparation method of the present invention has the characteristics of simple process steps, safety and easy control, easy availability of raw materials, less use of chemical reagents in the entire preparation process, less pollution to the environment, mild experimental conditions, short time consumption and low cost.

[0023] (3) When the Gd-doped rutile ruthenium dioxide nanosheets prepared by the present invention are used as oxygen evolution catalysts for electrolysis of water to produce hydrogen, they exhibit excellent (OER) oxygen evolution performance at 10 mA cm -2 It achieves an overpotential of only 230 mV at a current density of 2.5 % and has excellent mass-specific capacitance, excellent conductivity, a wide potential window, and high redox reversibility. Therefore, it has broad application prospects in the field of electrocatalysis (such as electrolysis of water to produce hydrogen). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 TEM image of the Gd-RuO2 composite material prepared in Example 1;

[0026] Figure 2 TEM mapping image of the Gd-RuO2 composite material prepared in Example 1;

[0027] Figure 3 is the XRD pattern of the Gd-RuO2 composite material prepared in Example 1;

[0028] Figure 4 Polarization curves of the Gd-RuO2 composite material (denoted as Gd-RuO2 in the figure) prepared in Example 1 and commercially available RuO2 (denoted as C-RuO2 in the figure) when used as anode catalysts for water electrolysis;

[0029] Figure 5 The polarization curve diagram of the Gd-RuO2 composite material obtained in Example 1-2 and Comparative Example 1-2 when used as an anode catalyst for water electrolysis;

[0030] Figure 6This is a polarization curve diagram of the Gd-RuO2 composite material prepared in Example 1-3 when used as an anode catalyst for water electrolysis. DETAILED DESCRIPTION

[0031] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.

[0032] Example 1

[0033] A method for preparing Gd-doped rutile ruthenium dioxide nanosheets comprises the following steps:

[0034] S1. Preparation of precursor solution:

[0035] 0.1 g RuCl3 and 0.002 g GdN3O9 were added to 25 ml anhydrous ethanol and ultrasonically treated for 15 min to obtain a precursor solution;

[0036] Preparation of S2, Gd-RuO2 composite material, i.e. Gd-doped rutile ruthenium dioxide:

[0037] The obtained precursor solution was added into a container containing 50g NaCl, stirred and reacted at 80℃ for 4h. After the reaction, the obtained reaction product was washed, centrifuged, and then placed in a drying oven at 60℃ for 12h, and then calcined and annealed at 450℃ in air to obtain a Gd-RuO2 composite material. The SEM, SEM mapping, TEM and XRD spectrum results are shown in Figure 1-4 .

[0038] Example 2

[0039] A method for preparing Gd-doped rutile ruthenium dioxide nanosheets comprises the following steps:

[0040] S1. Preparation of precursor solution:

[0041] 0.1 g RuCl3 and 0.001 g GdN3O9 were added to 25 ml anhydrous ethanol and ultrasonically treated for 15 min to obtain a precursor solution;

[0042] Preparation of S2, Gd-RuO2 composite material, i.e. Gd-doped rutile ruthenium dioxide:

[0043] The obtained precursor solution was added into a container containing 50g NaCl, and the reaction was stirred at 80°C for 4h. After the reaction was completed, the reaction product was washed, centrifuged, and dried in a drying oven at 60°C for 12h, and then calcined and annealed at 450°C in air to obtain a Gd-RuO2 composite material.

[0044] Example 3

[0045] A method for preparing Gd-doped rutile ruthenium dioxide nanosheets comprises the following steps:

[0046] S1. Preparation of precursor solution:

[0047] 0.1 g RuCl3 and 0.003 g GdN3O9 were added to 25 ml anhydrous ethanol and ultrasonically treated for 15 min to obtain a precursor solution;

[0048] Preparation of S2, Gd-RuO2 composite material, i.e. Gd-doped rutile ruthenium dioxide:

[0049] The obtained precursor solution was added into a container containing 50g NaCl, and the reaction was stirred at 80°C for 4h. After the reaction was completed, the reaction product was washed, centrifuged, and dried in a drying oven at 60°C for 12h, and then calcined and annealed at 450°C in air to obtain a Gd-RuO2 composite material.

[0050] Example 4

[0051] A method for preparing Gd-doped rutile ruthenium dioxide nanosheets comprises the following steps:

[0052] S1. Preparation of precursor solution:

[0053] 0.1 g RuCl3 and 0.002 g GdN3O9 were added to 25 ml anhydrous ethanol and ultrasonically treated for 15 min to obtain a precursor solution;

[0054] Preparation of S2, Gd-RuO2 composite material, i.e. Gd-doped rutile ruthenium dioxide:

[0055] The obtained precursor solution was added into a container containing 50g NaCl, and the reaction was stirred at 80°C for 4h. After the reaction was completed, the obtained reaction product was washed, centrifuged, and then placed in a drying oven at 60°C for 12h, and then calcined and annealed at 350°C in air to obtain a Gd-RuO2 composite material.

[0056] Example 5

[0057] A method for preparing Gd-doped rutile ruthenium dioxide nanosheets comprises the following steps:

[0058] S1. Preparation of precursor solution:

[0059] 0.08 g RuCl3 and 0.002 g GdN3O9 were added to 30 ml methanol and ultrasonically treated for 35 min to obtain a precursor solution;

[0060] Preparation of S2, Gd-RuO2 composite material, i.e. Gd-doped rutile ruthenium dioxide:

[0061] The obtained precursor solution was added into a container containing 55g NaCl, and the reaction was stirred at 60°C for 3h. After the reaction was completed, the obtained reaction product was washed, centrifuged, and then placed in a drying oven at 60°C for 12h, and then calcined and annealed at 450°C in air to obtain a Gd-RuO2 composite material.

[0062] Example 6

[0063] A method for preparing Gd-doped rutile ruthenium dioxide nanosheets comprises the following steps:

[0064] S1. Preparation of precursor solution:

[0065] 0.12 g RuCl3 and 0.003 g GdN3O9 were added to 20 ml water and ultrasonically treated for 25 min to obtain a precursor solution;

[0066] Preparation of S2, Gd-RuO2 composite material, i.e. Gd-doped rutile ruthenium dioxide:

[0067] The obtained precursor solution was added into a container containing 45 g of NaCl, and the reaction was stirred at 90°C for 6 h. After the reaction was completed, the obtained reaction product was washed, centrifuged, and then placed in a drying oven at 70°C for 18 h. It was then calcined and annealed in air at 500°C to obtain a Gd-RuO2 composite material.

[0068] Comparative Example 1

[0069] The steps are basically the same as those in Example 1, except that 0 g of GdN3O9 is added.

[0070] Comparative Example 2

[0071] The steps are basically the same as those in Example 1, except that 0.004 g of GdN3O9 is added.

[0072] Comparative Example 3

[0073] The steps are basically the same as those in Example 1, except that the annealing is performed at 550° C. in air.

[0074] Depend on Figure 1The results show that the Gd-RuO2 composite material prepared in Example 1 of the present invention (at a scale of 200 nm) has a flaky microstructure.

[0075] Depend on Figure 2 The results show that the Gd-RuO2 composite material prepared in Example 1 of the present invention is successfully doped with the Gd element, and the KCl has been cleaned and has an obvious flaky microstructure.

[0076] Depend on Figure 3 The results show that diffraction peaks appear at 27.86° and 34.94°, corresponding to the (110) and (101) crystal planes of RuO2, respectively.

[0077] The Gd-RuO2 composite materials prepared in Examples 1-4 and Comparative Examples 2-3 of the present invention, the RuO2 nanomaterials without Gd doping prepared in Comparative Example 1, and commercially available RuO2 (referred to as C-RuO2) were used as catalysts for hydrogen production by electrolysis of water for oxygen evolution catalytic activity tests, and as controls. The electrochemical tests were carried out in an electrochemical workstation (CHI 660E) and a standard three-electrode system. The Hg2Cl / Hg (saturated KCl) electrode was used as the reference electrode, and the graphite rod was used as the OER counter electrode. The tests were carried out in a 0.1M HClO4 (pH=1) solution. All linear sweep voltammetry (LSV) curves were plotted at 5mV s -1 The scan rates were recorded without iR compensation. All potentials were calculated relative to the reversible hydrogen electrode (RHE) using the following equation:

[0078]

[0079] Results Figure 4-6 .

[0080] Depend on Figure 4-6 The results show that compared with commercially available RuO2, the Gd-RuO2 composite material prepared in Example 1 has a better oxygen evolution performance as a catalyst; compared with Comparative Examples 1-2, the Gd-RuO2 composite material prepared in Example 1 has a better oxygen evolution performance as a catalyst, at 10 mA·cm -2At a current density of , an overpotential of only 30 mV was achieved, and at the same time, it had excellent conductivity, a wide potential window, and a high degree of redox reversibility. This may be attributed to the fact that doping Gd in RuO2 will lead to the extension of the Ru-O bond length, causing the OER mechanism to change from LOM to AEM, thereby greatly improving the catalytic activity of the catalyst; while the results of Comparative Example 2 show that the doped Gd should not be too much, as too much will reduce its catalytic activity. This may be attributed to the fact that when the doping amount of Gd is too much, the Ru-O bond length will be too long, resulting in the dissolution of the Ru site. Compared with Comparative Example 3, the Gd-RuO2 composite materials obtained in Example 1 and Example 4 have better oxygen evolution performance as a catalyst, which indicates that the calcination annealing temperature should not be too high, as too high a temperature will cause RuO2 to agglomerate and thus seriously reduce its catalytic performance.

[0081] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. A method for preparing Gd-doped rutile ruthenium dioxide nanosheets, characterized in that: The following steps are involved: S1, dissolving RuCl3 and GdN3O9 in a solvent to prepare a precursor solution; S2. Add the obtained precursor solution into NaCl, stir to react, purify, calcine and anneal to obtain Gd-doped rutile ruthenium dioxide nanosheets.

2. The method for preparing the Gd-doped rutile ruthenium dioxide nanosheets according to claim 1, characterized in that: The mass volume ratio of RuCl3, GdN3O9, solvent and NaCl is in the range of 0.08g-0.12g: 0.001g-0.003g: 20ml-30ml: 45g-55g.

3. The method for preparing the Gd-doped rutile ruthenium dioxide nanosheets according to claim 1, characterized in that: In step S2, before adding the obtained precursor solution into NaCl, the precursor solution is ultrasonically treated for 15 to 35 minutes.

4. The method for preparing the Gd-doped rutile ruthenium dioxide nanosheets according to claim 1, characterized in that: In step S2, the temperature during the stirring reaction is 60-90°C, and the stirring reaction time is 3-6h.

5. The method for preparing the Gd-doped rutile ruthenium dioxide nanosheets according to claim 1, characterized in that: In step S2, the purification includes: washing, centrifuging and drying the reaction product.

6. The method for preparing the Gd-doped rutile ruthenium dioxide nanosheets according to claim 5, characterized in that: The drying temperature is 60-70° C., and the drying time is 12-18 hours.

7. The method for preparing Gd-doped rutile ruthenium dioxide nanosheets according to claim 1, characterized in that: The calcination and annealing treatment is carried out in air at a temperature of 350-500°C.

8. A Gd-doped rutile ruthenium dioxide nanosheet prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Gd-doped rutile ruthenium dioxide nanosheet as claimed in claim 8 as a catalyst in hydrogen production by water electrolysis.

Citation Information

Patent Citations

  • Rare earth element doped RuO2 material as well as preparation method and application thereof

    CN118127561A

  • Ru-based oxide catalyst and preparation method and application thereof

    CN118186459A

  • Method for preparing M-RuO2 nanoparticles through vapor deposition

    CN118996513A

  • Ultrafine nickel-doped ruthenium oxide water electrolysis hydrogen production catalyst prepared by template method and application of ultrafine nickel-doped ruthenium oxide water electrolysis hydrogen production catalyst

    CN119121297A

  • Large-current-density long-term stable electro-catalytic oxygen evolution catalyst as well as preparation method and application thereof

    CN119194487A

Cited By

  • Anode structure of proton exchange membrane water electrolysis cell as well as preparation method and application of anode structure

    CN121496455A